2022
DOI: 10.1111/jbi.14334
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocongruent phylogeography reflects unique responses to environmental perturbations in a biodiversity hotspot

Abstract: Aim: Comparative phylogeographic studies provide important insights into the biogeographic processes shaping regional patterns of diversity. Yet, comparative studies are lacking for southern African herpetofauna, despite their high diversity. We statistically compare phylogeographic structure and divergence-time estimates among five co-distributed forest-living herpetofaunal taxa to assess rivers, climatic refugia and climatic gradients as congruent drivers of phylogeographic diversity.Location: Maputoland-Pon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Consequently, old lineages will diverge even more, while previously undifferentiated widely distributed taxa will only start to diverge from their conspecifics in other refugia. Thus, it is not unexpected that a recent analysis of phylogeographic congruence for herpetofauna from South Africa demonstrated that broad spatial congruence of co-distributed taxa is actually uncorrelated (Busschau et al 2022). We therefore encourage phylogeographic investigators to exercise caution in providing wholesale interpretations regarding congruency of patterns and to give careful attention to timing of diversification events and examine alternatives, and to propose hypotheses that are falsifiable.…”
Section: Discussionmentioning
confidence: 92%
“…Consequently, old lineages will diverge even more, while previously undifferentiated widely distributed taxa will only start to diverge from their conspecifics in other refugia. Thus, it is not unexpected that a recent analysis of phylogeographic congruence for herpetofauna from South Africa demonstrated that broad spatial congruence of co-distributed taxa is actually uncorrelated (Busschau et al 2022). We therefore encourage phylogeographic investigators to exercise caution in providing wholesale interpretations regarding congruency of patterns and to give careful attention to timing of diversification events and examine alternatives, and to propose hypotheses that are falsifiable.…”
Section: Discussionmentioning
confidence: 92%
“…Aridification increased and the contraction of the forest biome persisted during the Pliocene to Pleistocene, further promoting cladogenesis among the velvet worm fauna of South Africa. In addition, the Miocene, Pliocene, and Pleistocene epochs represent periods of major cladogenesis in several other South African faunal groups (e.g., Barnes et al, 2020;Busschau et al, 2019Busschau et al, , 2021Busschau et al, , 2022Tolley et al, 2011Tolley et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…A revision of the O. kwazululandi s. l. species complex is outside of the scope of the present study but will be initiated in future. In addition, a recent comparative phylogeographic study by Busschau et al (2022) (Garrick et al, 2004). We are now focusing on poorly sampled regions in an attempt to identify sympatric velvet worm species and assess their reproductive isolation using additional DNA sequence data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once our cladistic biogeographic analysis was completed, we employed the comprehensive phylogeny of Thomson et al (2021) to assess whether biogeographical patterns were synchronous or established episodically, over time (Morrone 2020). This was necessary because a shared pattern does not prove synchronicity (Donoghue and Moore 2003, Naka and Brumfield 2018, Busschau et al 2022. That is, the same biogeographical pattern can be repeated through time (e.g., Keck andNear 2010, Blanton et al 2013).…”
Section: Introductionmentioning
confidence: 99%